121 Effects of Total Dietary Fiber Content During Gestation on Sow Reproductive Performance. (12th April 2022) - Paz Portal, Ximena A; Rosero, David; Carter, Scott D; Wilcock, Pete
Abstract: The objective of this study was to investigate the effects of total dietary fiber (TDF) levels during gestation on sow and litter performance. A total of 397 (Camborough, PIC) individual-housed sows were used. Sows were balanced by parity (P4-P10) and body condition score (BCS, 1-5) at breeding and allocated to 2 treatments: Low Fiber (TDF = 9%, LF) or High Fiber (TDF = 18%, HF) with similar insoluble to soluble fiber ratios 7.4 and 7.5 respectively. During gestation, all sows were fed according to their BCS (BCS 1 and 2 = 2.7 kg/d, BCS 3 = 2kg/d and BCS 4 and 5 = 1.6 kg/d). From d 90 of gestation thin sows (BCS 1 or 2) received an additional 0.9 kg/d. During lactation sows received a common diet, 1.81 kg/d pre-farrow, and then ad libitum. Diets were milo based with wheat midds and soy hulls as fiber sources. Dietary treatments were isonutrient and isocaloric and formulated to meet or exceed NRC (2012) nutrients. Data were analyzed for main effects of treatment and within body condition category. Overall, sows that received the LF diet were heavier at placement in lactation (306.6 and 280.6 kg; P = 0.012, for LF and HF, respectively). Similarly, the estimated post-partum BW was heavier for those fed the LF diet (283.1 and 256.1 kg; P = 0.008) and at wean BW (271.3 and 257.1 kg; P = 0.003). However, sows fed a HF gestation diet tended to lose less weight during lactation (17.0 and 4.0 kg; P = 0.080). There were no differences for total born ( P = 0.767), born alive ( P = 0.821), stillborn ( P = 0.850) or weaned pigs ( P = 0.620). In conclusion, elevating TDF during gestation did not improve litter performance, but did reduce weight and body condition loss during lactation.